PERILAKU BELANJA ONLINE DAN OFFLINE IBU RUMAH TANGGA DI DAERAH PESISIR - Nugraha, Tryan; Aminuddin, Ahsani Taqwim; Amaliah, Desi (Universitas Pakuan, 2025)
This study analyzes the online and offline shopping behavior of housewives in coastal areas, particularly in Palabuhanratu. Using a survey approach and focus group discussions (FGDs), this research explores the factors influencing shopping decisions, e-commerce platform preferences, and obstacles to adopting online shopping. The findings reveal that although online shopping is increasingly popular due to accessibility and attractive promotions, most housewives still have relatively low transaction intensity. Trust in product quality, limitations in digital payment methods, and the need for a social shopping experience are key factors that lead many respondents to prefer offline shopping. Shopee emerged as the most widely used platform, supported by aggressive marketing strategies and flexible transaction features. However, cash-on-delivery (COD) remains a popular payment method, indicating that many consumers still lack full confidence in digital transactions. Additionally, the study highlights that shopping is not just an economic transaction but also a social activity that impacts consumers' emotional well-being. Thus, while e-commerce continues to grow, the in-store shopping experience remains an essential aspect that is difficult to replace among housewives in coastal communities.